2014
DOI: 10.1007/978-3-642-53734-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Information Dynamics in Swarms

Abstract: We propose a novel, information theoretic characterization of dynamics within swarms, through explicitly measuring the extent of collective communications and tracing collective memory. These elements of distributed computation provide complementary views into the capacity for swarm coherence and reorganization. The approach deals with both global and local information dynamics ultimately discovering diverse ways in which an individual's location within the group is related to its information processing role.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Average and local active information have been used been used to understand information storage in biological systems as diverse as swarm behavior [418][419][420], gene regulatory networks [421], neural information processing [40,41], and to evolve artificial information processing systems [415]. Application to neural information processing is particularly relevant to the cancer problem since the measurements of voltage potential tracking V mem across populations of cells is similar in data content to that acquired by fMRI of brain tissue.…”
Section: Information Storagementioning
confidence: 99%
“…Average and local active information have been used been used to understand information storage in biological systems as diverse as swarm behavior [418][419][420], gene regulatory networks [421], neural information processing [40,41], and to evolve artificial information processing systems [415]. Application to neural information processing is particularly relevant to the cancer problem since the measurements of voltage potential tracking V mem across populations of cells is similar in data content to that acquired by fMRI of brain tissue.…”
Section: Information Storagementioning
confidence: 99%
“…We could use the principles in information theory to solve the problem in self-organization. He also gave two examples of the application of the information theory in self-organization systems: and Transfer Entropy (TE) [40,22]. This work discovers how an individual's position is related to its information processing role and provides the first information-theoretic evidence that the information cascades occur in waves rippling through the swarm.…”
Section: Case Study Ii: Extension For Two Individuals Systemmentioning
confidence: 98%
“…Information theoretic measures such as information storage or information modification could prove useful to CASN analysis as well. Although these ideas require more research relative to CASN specifically, other disciplines have found correlations between information theoretic measures and the concepts of self-organization and emergence [32,33], network stability [34,35], interdependencies [36], and distributed computation [37] in many types of networks. Being able to quantify these behaviors and characteristics for CASN would enable significant advances in a research area that has been primarily grounded in empirical data, models and simulations, and social network analysis.…”
Section: Transfer Entropy Applicationmentioning
confidence: 99%